Argumentation features and essay quality: Exploring relationships and incidence counts - Crossley, Scott; Tian, Yu; Wan, Qian (Journal of Writing Research, 2022)
This study examines links between human ratings of writing quality and the incidence of argumentative features (e.g., claims, data) in persuasive essays along with relationships among these features and their distance from one another within an essay. The goal is to better understand how argumentation elements in persuasive essays combine to model human ratings of essay quality. The study finds that, in most cases, it is not the presence of argumentation features that is predictive of writing quality but rather the relationships between superordinate and subordinate features, parallel features, and the distances between features. This finding has not only theoretical value but also practical value in terms of pedagogical approaches and automated writing feedback.